Electro-mechanical and mechano-electrical interactions in healthy and drug-induced LQTS rabbit hearts. (24th May 2021) - Lewetag, R; Hornyik, T; Jacobi, S; Moss, R; Pilia, N; Menza, M; Perez-Feliz, S; Bode, C; Seemann, G; Odening, KE
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): German Research Foundation Background: Electrical and mechanical heterogeneities and their interactions (electro-mechanical and mechano-electrical coupling; EMC / MEC) are essential for normal cardiac function. Alterations in these can result in increased arrhythmia formation. Purpose: With this study, we aim to investigate EMC and MEC under physiological and pathological conditions to better understand their roles in arrhythmia development. Methods: Multi-channel ECG and TPM-MRI were used to measure regional differences in EMC in healthy ("control") and IKr-blocker E-4031 induced acute LQTS ("E-4031") rabbit hearts in vivo. MEC was studied in both groups by acutely changing mechanical function (increased preload by 6 ml/kg BW bolus of NaCl). Results: In acute LQTS hearts (E-4031 10µg/kg bolus + 1µg/(kg*min) iv), cardiac repolarization was markedly prolonged compared to healthy controls, (p < 0.0001; n = 13), with increased QT-dispersion (Max-Min), a marker for regional heterogeneity of repolarization (p < 0.01; n = 13). Changing electrical function by E-4031 resulted in changes of mechanical features (EMC): in acute LQTS hearts, diastolic longitudinal velocity (Vz) was reduced in all basal (p = 0.003; n = 19) and 4/6 mid segments (p = 0.006; n = 19). Longitudinal diastolic TTP was prolonged significantly in 5/6 basal and 4/6 mid segments by E-4031. These alterations led to an increased apicobasal heterogeneity of longitudinal contraction duration (basal-apical Vz_dia_TTP [ms] 2.9 ± 10.6 vs. 21.1 ± 21.3; p = 0.01; n = 9). Increased preload acutely prolonged QTc in both "control" and "E-4031" hearts ('control' 156.6 ± 11.6 to 198.3 ± 20.3; p < 0.0001 vs. 'E-4031' 193.9 ± 19.6 to 256.0 ± 37.5; p < 0.0001; n = 13) (MEC). This effect was more pronounced in "E-4031" acute LQTS hearts than in healthy hearts (Figure 1; delta QTc [ms] 'control' 41.6 ± 14.9 vs. 'E4031' 62.1 ± 32.1; p < 0.006, n = 13). QT-dispersion (Max-Min) was increased significantly upon mechanical change only in "E-4031" ('E-4031' 25.8 ± 5.5 to 32.7 ± 12.3; p < 0.03, n = 13). Conclusion: E-4031-induced changes in electrical function resulted in marked alterations in mechanical features via EMC. Similarly, acute changes in mechanical function (increased preload) resulted in electrical changes via MEC. Importantly, QT-prolonging effects of acutely increased preload, as well as its effects on regional heterogeneity of repolarization, were more pronounced in E-4031-induced acute LQTS hearts, indicating that cardiac repolarization in LQTS may be more susceptible to acute MEC effects than in healthy hearts. Acute MEC effects may thus play an additional role in LQT-related arrhythmogenesis.